Evasão na educação superior: tendências da produção acadêmica - Meireles, Paulo Victor Bussad (2024)
This dissertation, linked to the Postgraduate Program in Education at the State University of Western Paraná (UNIOESTE), in the line of Culture, Educational Processes and Teacher Training, aims to analyze, based on scientific research, the understanding of the phenomenon of evasion in Higher Education Institutions in Brazil. This study discusses methodological issues in research in the area of Human Sciences, specifically focused on education, and problematizes the extent to which the standardization of keywords and descriptors can impact the choice of a given theoretical corpus. It reveals the reasons, the profile of the students and what is needed to minimize dropouts in higher education. We sought to identify which dimensions were addressed in studies dealing with student dropout rates in Brazilian public higher education institutions in the period 2007-2023, indexed in the Scopus database, and whether these studies investigated the reasons and proposed strategies to overcome dropout rates in higher education. The methodology is based on bibliographic research combined with reflection on the data collection process in journals and repositories. Initially, through bibliometric analysis, it was possible to identify the intellectual structure of publications indexed in the Scopus database that had as their object of study dropout in higher education. Subsequently, through the methodological procedure called state of knowledge, it was possible to reorganize the corpus of analysis into categories, identify the presence of new information, and establish considerations through syntheses. The category "reasons for evasion" pointed to a diversity of reasons of the personal, interpersonal, institutional, professional, socioeconomic and autonomy types. In the category “actions and strategies to mitigate dropout”, despite the scarcity of studies for this category, the actions and strategies were characterized by aiming at structural reforms, such as making courses more flexible and adapting physical and technological infrastructure, and personalized and adaptive interventions such as the learning styles methodology, opening special classes, updating and readapting the course’s pedagogical project, expanding psychopedagogical monitoring and guidance, and disseminating possibilities for professional activity.